Thoughts on Ecumenical Dialogue in the Digital Age - Farrell, Brian (The ecumenical review, 2021)
In the time of COVID-19, because of travel and meeting restrictions, all kinds of meetings are taking place through videoconferencing. The global experience of continuing to work while observing social distancing guidelines is slowly removing the technological, normative, and required-knowledge resistance that during normal circumstances would have hindered the global diffusion of videoconferencing we are now seeing. Videoconferencing is a welcome tool that has provided an opportunity for creating a sense of face-to-face interaction during a time when physical presence is often not possible. Nevertheless, this tool can present specific challenges to interpersonal interaction. This article discusses the challenges posed by videoconferencing technology in the specific case of ecumenical dialogue. Churches engaged in ecumenical dialogue need to ask how the search for understanding and agreement can succeed in the era of digital interaction.